2014
DOI: 10.12691/jfnr-2-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Color Additiveson Antioxidant Functions and Bioelement Contents of Liver, Kidney and Brain Tissues in Rats

Abstract: A number of chemical food coloring additives are added during processing to improve the appearance of thef oods and drinks. Tartrazine and carmoisine are organic azo dyes widely used in food products, drugs and cosmetics. The present study conducted to evaluate the effects of these food coloring additives via determination of bioelements, oxidant and antioxidant levels in liver, kidney, brain tissues and measurement of antioxidantvitamin levels in serum of rats. Animals were administered in high and low doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…Moreover, low dose tartrazine induced reduced liver zinc content and high dose tartrazine has the same result in kidney, this may be due unsaturated fatty acids peroxidation in cell membranes by ROS produced during tartrazine administration, resulting in a decrease of membrane flexibility and disturbance in cell function and integrity which affected the pumping and selection of activities of membranes and the level of bioelements may be altered in tissues (Cemek et al, 2014).…”
Section: Effect Of Tartrazine On Tissues Bioelement Contentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, low dose tartrazine induced reduced liver zinc content and high dose tartrazine has the same result in kidney, this may be due unsaturated fatty acids peroxidation in cell membranes by ROS produced during tartrazine administration, resulting in a decrease of membrane flexibility and disturbance in cell function and integrity which affected the pumping and selection of activities of membranes and the level of bioelements may be altered in tissues (Cemek et al, 2014).…”
Section: Effect Of Tartrazine On Tissues Bioelement Contentsmentioning
confidence: 97%
“…In a few manuscripts on biolement and tartrazine, there were reports on significant changes in levels of bioelements in rats' liver, kidney and brain tissues exposed to tartrazine (Cemek et al, 2014). The changes include increased Cu and iron level in renal tissue, which is important because copper accumulation in the tissues leads to Wilson's disease and hepatic cirrhosis (Shazia et al, 2012); this effect may be due to binding of copper and iron to the artificial food colorants, resulting in its tissues accumulation (Stevens et al, 2013).…”
Section: Effect Of Tartrazine On Tissues Bioelement Contentsmentioning
confidence: 99%
“…Depletion of GSH puts cells at oxidative risks. Cemek et al (2014) concluded that tartrazine and carmoisine concentrations were not sufficient to change the GSH levels in tissues.…”
Section: Effect Of Natural and Synthetic Colorants On Liver Lipid Permentioning
confidence: 99%
“…It has been concluded that food color (tartrazine and carmoisine) affect and alter bioelements levels in vital organs e.g. liver, kidney and brain (Cemek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tartrazine administration for 60 days to male rats reduced testicular concentrations of superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase (Visweswaran and Krishnamoorthy 2012). These synthetic colorants can alter concentrations of zinc, iron, copper and manganese which are all essential cofactors for antioxidant enzymes (Cemek et al 2014;Visweswaran and Krishnamoorthy 2012). Food colourings are also associated with increased immune reactivity which may be another mechanism associated with O&NS (Vojdani and Vojdani 2015).…”
Section: Potential Causes Of Oandns In Adhdmentioning
confidence: 99%